Thermodynamic properties of the liquid Bi-Cu-Sn lead-free solder alloys - Kopyto M.; Garzel G.; Zabdyr L.A. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The electromotive force measurement method was employed to determine the thermodynamic properties of liquid Bi-Cu-Sn alloys using solid electrolyte galvanic cells as shown below: Kanthal+Re, Bi-Cu-Sn, SnO2 | Yttria Stabilized Zirconia | air, Pt, Po2=0.2:1 atm Measurements were carried out for three cross-sections with constant Bi/Cu ratio equal to: 1/3, 1 and 3 and for various tin content varying every 10%, resulting in a total of 26 different alloy compositions. The temperature of the measurements varied within the range from 973 to 1325 K. A linear dependence of the e.m.f. on temperature was observed for all alloy compositions and the appropriate line equations were derived. Tin activities were calculated as function of composition and temperature. Results were presented in tables and figures.